Experimental study on the repair of peripheral nerve injuries via simultaneously coapting the proximal and distal ends of peripheral nerves to the side of nearby intact nerves - Li, Dongdong; Yang, Qi; Liu, Xin; Jia, Jing; Liu, Guangbo; Bai, Kewen; Jia, Shicheng; Peng, Jun; Yu, Fei (Frontiers in Neurology, 2023)
Introduction Peripheral nerve defect is a difficult disease to treat in clinical practice. End-to-side anastomosis is a useful method to treat it. At present, the end-to-side anastomosis method does not involve the proximal nerve, which results in a waste of proximal donor nerves, and even the formation of traumatic neuromas at the proximal end. The patients suffer from traumatic neuralgia and the curative effect is unsatisfactory. Methods In this study, an improved end-to-side anastomosis technique was proposed in this study: both the proximal and distal ends of the damaged common peroneal nerve were sutured to an adjacent normal tibial nerve. Moreover, the possible role and mechanism of the proposed technique were explained at the physiological and anatomical levels. In this study, a 10 mm common peroneal nerve defect was made in SD rats, and the rats were randomly divided into three groups. In Group I, the distal end of the common peroneal nerve was attached end-to-side to the fenestrated tibial nerve adventitia, and the proximal end was ligated and fixed in the nearby muscle. In Group II, the tibial nerve adventitia was fenestrated and the epineurial end-to-end anastomosis surgery was performed to suture the proximal and distal ends of the common peroneal nerve. Rats in Group III were taken as control and received sham operation. Twelve weeks after the operation, the recovery of the repaired nerve and distal effector functions were examined by the sciatic functional index, electrophysiology, osmic acid staining, the muscle wet weight ratio, and the muscle fiber cross-sectional area. Results It was found that these results in Group II were similar to those in Group III, but better than those in Group I. Through retrograde tracing of neurons and Electrophysiological examination in Group II, the study also found that the proximal common peroneal nerve also could establish a connection with tibialis anterior, even gastrocnemius. Discussion Therefore, it is inferred that fostering both the proximal and distal ends of defective peripheral nerves on normal peripheral nerves using the end-to-side anastomosis technique is a more effective approach to repairing injured nerves.